The status of the amphibian nomina created by Merrem (1820) and Ritgen (1828) - Dubois, Alain; Ohler, Annemarie (Zootaxa, 2009)
In a poorly known work, Ritgen (1828) published an unconventional taxonomy and nomenclature of amphibians and reptiles. This work was an expansion of the taxonomic system of Merrem (1820) for these animals. After a survey of the nomenclatural status of the few supraspecific nomina used in Merrem (1820) for amphibians, in the current sense of this term, we ascertain the nomenclatural status of all the nomina created by Ritgen (1828) for genera and higher taxa including these animals. We designate nucleospecies (type-species) for his five new generic nomina, which results in making them invalid junior synonyms of nomina currently considered valid. Among the 21 nomina which he created for higher amphibian taxa, two prove to be the valid senior synonyms, following the Rules suggested by Dubois (2006a), of nomina used by Frost et al. (2006), and the same is true for two other such nomina created earlier by Merrem (1820). This example shows how these Rules allow to stabilize automatically and objectively the higher nomenclature in zoology, without recourse to interpretations, “opinion” or use of the “principle of authority”, which currently predominates in this field.